Adjuvant Palbociclib for Early Breast Cancer: The PALLAS Trial Results (ABCSG-42/AFT-05/BIG-14-03). Issue 3 (20th January 2022) - Gnant, Michael; Dueck, Amylou C.; Frantal, Sophie; Martin, Miguel; Burstein, Hal J.; Greil, Richard; Fox, Peter; Wolff, Antonio C.; Chan, Arlene; Winer, Eric P.; Pfeiler, Georg; Miller, Kathy D.; et al.
Abstract : PURPOSE: Palbociclib is a cyclin-dependent kinase 4 and 6 inhibitor approved for advanced breast cancer. In the adjuvant setting, the potential value of adding palbociclib to endocrine therapy for hormone receptor–positive breast cancer has not been confirmed. PATIENTS AND METHODS: In the prospective, randomized, phase III PALLAS trial, patients with hormone receptor–positive, human epidermal growth factor receptor 2–negative early breast cancer were randomly assigned to receive 2 years of palbociclib (125 mg orally once daily, days 1-21 of a 28-day cycle) with adjuvant endocrine therapy or adjuvant endocrine therapy alone (for at least 5 years). The primary end point of the study was invasive disease-free survival (iDFS); secondary end points were invasive breast cancer–free survival, distant recurrence-free survival, locoregional cancer-free survival, and overall survival. RESULTS: Among 5, 796 patients enrolled at 406 centers in 21 countries worldwide over 3 years, 5, 761 were included in the intention-to-treat population. At the final protocol-defined analysis, at a median follow-up of 31 months, iDFS events occurred in 253 of 2, 884 (8.8%) patients who received palbociclib plus endocrine therapy and in 263 of 2, 877 (9.1%) patients who received endocrine therapy alone, with similar results between the two treatment groups (iDFS at 4 years: 84.2% v 84.5%; hazard ratio, 0.96; CI, 0.81 to 1.14; P = .65). No significant differences were observed for secondary time-to-event end points, and subgroup analyses did not show any differences by subgroup. There were no new safety signals for palbociclib in this trial. CONCLUSION: At this final analysis of the PALLAS trial, the addition of adjuvant palbociclib to standard endocrine therapy did not improve outcomes over endocrine therapy alone in patients with early hormone receptor–positive breast cancer. Abstract :